(untitled) (Tzintzun, Revista de Estudios Históricos, 2023)
The article studies the confiscation process in the state of Guanajuato and aims to demonstrate the problems that occurred in the collection of the domain transfer tax, from 1856 to 1861, a period in which the main farms of the entity were alienated. It is shown that the income generated was not as expected by the federal government, due to political problems and the fight between liberals and conservatives, in addition to the resistance of taxpayers to pay the alcabala, either for fear of losing that money or for the inability to pay it due to instability, as was the case with tax collection in general.